Prognostic utility of serum CRP levels in combination with CURB-65 in patients with clinically suspected sepsis: a decision curve analysis. Issue 4 (28th April 2015) - Yamamoto, Shungo; Yamazaki, Shin; Shimizu, Tsunehiro; Takeshima, Taro; Fukuma, Shingo; Yamamoto, Yosuke; Tochitani, Kentaro; Tsuchido, Yasuhiro; Shinohara, Koh; Fukuhara, Shunichi
Abstract : Objectives: The prognostic utility of serum C reactive protein (CRP) alone in sepsis is controversial. We used decision curve analysis (DCA) to evaluate the clinical usefulness of combining serum CRP levels with the CUBR-65 score in patients with suspected sepsis. Design: Retrospective cohort study. Setting: Emergency department (ED) of an urban teaching hospital in Japan. Participants: Consecutive ED patients over 15 years of age who were admitted to the hospital after having a blood culture taken in the ED between 1 January 2010 and 31 December 2012. Main outcome measures: 30-day in-hospital mortality. Results: Data from 1262 patients were analysed for score evaluation. The 30-day in-hospital mortality was 8.4%. Multivariable analysis showed that serum CRP ≥150 mg/L was an independent predictor of death (adjusted OR 2.0; 95% CI 1.3 to 3.1). We compared the predictive performance of CURB-65 with the performance of a modified CURB-65 with that included CRP (≥150 mg/L) to quantify the clinical usefulness of combining serum CRP with CURB-65. The areas under the receiver operating characteristics curves of CURB-65 and a modified CURB-65 were 0.76 (95% CI 0.72 to 0.80) and 0.77 (95% CI 0.72 to 0.81), respectively. Both models had good calibration for mortality and were useful among threshold probabilities from 0% to 30%. However, while incorporating CRP into CURB-65 yielded a significant category-free net reclassification improvement of 0.387 (95% CI 0.193 to 0.582) and integrated discrimination improvement of 0.015 (95% CI 0.004 to 0.027), DCA showed that CURB-65 and the modified CURB-65 score had comparable net benefits for prediction of mortality. Conclusions: Measurement of serum CRP added limited clinical usefulness to CURB-65 in predicting mortality in patients with clinically suspected sepsis, regardless of the source.